E-commerce: problems and challenges on tax administration and collection / Wan Nazri Md Shamsuddin - Md Shamsuddin, Wan Nazri (2013)
Electronic Commerce (e-commerce) has become the trendy tools for businesses all around the world nowadays. Ever since 1970’s, we have seen tremendous growth of e-commerce.However, with the growth in trade across border thru e-commerce there are arguments that the tax system is conventional to the 21st century technologies. Evidently, referring to the guideline on taxation of electronic commerce produce by the Inland Revenue Board on 1 January 2013, (Sec 4, Subsection 4.1) “There are no specific provisions under the ITA 1967 which address e-commerce transactions. Therefore, the general provisions and interpretations of the ITA 1967 will be applicable”.Existing tax rules are designed for a face-to-face conventional interaction scenario between customer and supplier. New development of business method triggered the important of imposing taxes on profitable income. Cyberspace trading and cross border trading are engaged in a trade without having a physical presence which has altered the normality of conventional tax rule, which is the recognition of physical existence (permanent establishment). This has led the government in many countries to face a new challenge of tax problems i.e. loss of tax revenue. The aim of this study (i) is to determine whether the conventional tax regime adequately supports the proliferation of e-commerce; (ii) to discover existing and emerging problems in e-commerce to the present taxpayers, tax agents and tax administrators and (iii) to investigate potential challenges to the tax system as a result of the expansion in e-commerce. This study is based on primary data from the questionnaires handed over to a group of sample from the officers’ Inland Revenue Board of Malaysia (IRBM), academicians, tax payer and tax practitioners.